(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: the International Physical Activity Questionnaire (IPAQ) is an instrument for crossnational monitoring of physical activity and inactivity. The aim of the study was the reliability evaluation of the Italian telephone-administered IPAQ version in Rome. Methods: the IPAQ short form (IPAQ-SF), consisting of 7 items, was administered. The responses, used to compute Metabolic Equivalent Task (MET in minutes per week), were processed to analyze the internal consistency. Standardized Cronbach’s alpha was used for reliability estimation. Results: a total of 133 adults (51 males and 82 females) participated in the study, with a mean age of 51 years (SD=19). The mean MET was 4 130, corresponding to good physical activity levels. The standardized Cronbach’s alpha on 6 items, concerning time spent on vigorous and moderate activity and walking, was 0.614. Conclusions: according to the findings from other countries, the Italian IPAQ-SF has acceptable measurement properties, as good as other established self-reports. The IPAQ-SF has a questionable reliability as previously reported, but the results of the present pilot study are promising and suggest that these instruments can be used to compare population estimates of physical activity.